PENGARUH METODE OUTDOOR LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN IPA KELAS V SD NEGERI 23 GELUMBANG - Ela Aprilia; M. Taheri Akbar; Arief Kuswidyanarko (LPPM Universitas Cipta Mandiri, 2025)
This research aims to find out the influence of outdoor learning methods on the critical thinking ability of students in learning IPA grade V SD State 23 Ballumbang. This research is undermined by the critical thinking ability of students very lacking in the learning of IPA class V SD State 23 Balumbang. The type of research used is quantitative research using the Quasi Experimental Design method. The design in the research is Nonequivalent Control Group Design. The sample for this study was a V.A class of 25 students and a VB class of 24 students. The data collection technique in this study is observation and testing using an essay question of 5 questions. The data analysis technique in the study was processed using the normality test obtained a sig value of 0.141 > 0.05, followed by the homogeneity test of 0.113 > 0.05 and the Independent Sample T-Test obtaining a sig. (2-tailed) of 0.006 < 0.05. So can be drawn the conclusion that Ha accepted, means there is a significant influence of outdoor learning methods on the ability of critical thinking students in learning IPA grade V SD.